Low-emission economy - evolution or necessity = Gospodarka niskoemisyjna - ewolucja czy konieczność - Godzisz, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A low carbon economy serves to provide economic, social and environmental benefits from measures to reduce emissions of pollutants. The implementation of a low carbon economy in Poland results from the need to reduce emissions of greenhouse gases and other air pollutants while reducing the share of coal in energy production, introducing innovative technologies and improving energy efficiency as well as increasing the standard of living of the society. This is a difficult task due to the large use of coal in energy production.
Keywords: low carbon economy; plans for low-emission economy; air pollution; energetic efficiency; reduction of gas emissions; greenhouse gases; gospodarka niskoemisyjna; plany gospodarki niskoemisyjnej; zanieczyszczenia powietrza; efektywność energetyczna; redukcja emisji gazów; gazy cieplarniane